Digital technology and the impact on communication language and mastery of generation X and Y for correspondence language - Zainon Hamzah, Zaitul Azma; Kamarudin, Kamariah; Hajimaming, Pabiyah; Yaakob, Nor Azuwan (PalArch Foundation, 2020)
In today’s epoch of digital technology, the way generations communicate or interact is also varied. The accelerated presence of digital communication technology in recent times affects the language and communication of Generation X and Y in institutions and organisations. Hence, this research explained the impact of digital technology on communication language and language proficiency among Generation X and Y, as well as described the steps to bridge the communication gap between Generation X and Y as aresult of the advancement of digital technology in communication today. Empirical studies were administered using the interview method. Unstructured interviews were conducted in groups by location. A sum of 65 people among Generations X and Y were chosen as interview respondents employing purposeful sampling techniques. The outcomes of the study concluded that digital technology also affects the communication language of Generation X and Y. Thus, it is evident that it holds an impact on the mastery of the language of correspondence among Generation Y in the workplace. Moreover, digital technology contributes to creating a generation gap when there are differences in language and communication, differences in age and personality, openness, level of educationand life experience between Generations X and Y. Consequently, before the generation gap becomes critical, some measures must be taken such as conducting workshops, forums and social activities outside the office to bridge the generation gap between Generation X and Y. Furthermore, Generation X must be able to accept the presence of communication language variations in the digital age. At the same time, Generation Y must master the language of correspondence communicated officially at work. Generations X and Y also must review the language of communication in digital communication and communicate face-to-face for the sake of mutual harmony in institutions and organisations.